Design and synthesis of two armed molecular receptor for recognition of Gd3+ metal ion and its computational study. (10th August 2018) - Mohan, Brij; Modi, Krunal; Patel, Chirag; Bhatia, Pankaj; Kumar, Ashwani; Sharma, Harish Kumar
Abstract : New receptorP henylene‐B is‐M ethylfuran‐yl‐2‐M ethyeleA cetohydrazide (PBMMA ) has been synthesized by condensation of hydrazide and 5‐methyl furfural. Synthesized receptor has been fully characterized by IR, 1 H NMR, 13 C NMR, mass spectroscopic and thermo gravimetric analysis. The receptorPBMMA shows selective recognition potential towards Gd 3+ ion when tested with several metal ions such as Na +, K +, Mg 2+, Cu 2+, Cd 2+, Hg 2+, Y 3+, La 3+, Eu 3+, Sm 3+, Gd 3+, Re 6+ and Th 4+ ion as their sulfates by UV–visible and fluorescence spectroscopic studies. Binding nature ofPBMMA with Gd 3+ ion was further studied by mass spectroscopic and cyclic voltammetric studies. The stoichiometry ofPBMMA‐ Gd 3+ ion has been established, 1:1 by Benesi‐Hildebrand plot method and method of continuous variation (Job's plot) with association affinity K = 6.491 × 10 4 M −1 . In addition to these, molecular docking, molecular dynamic stimulation and binding energy of complex; through Density Function theory −595.66 kcal/mol has also indication of strong binding. The electron transfer energy of Higher occupied molecular orbital (HOMO) to Lower unoccupied molecular orbital (LUMO) is about 4.186 eV and 295 nm for PBMMA‐Gd 3+ Complex. Abstract : A new two armed molecular receptor 2, 2′‐(1, 3‐phenylenebis (oxy))bis (N′‐((E)‐(5‐methylfuran‐2‐yl)methylene)acetohydrazide) has been synthesized. The synthesized compound has been established as a good receptor for Gd 3+ ion among various metal ions based on UV‐visible, fluorescence, mass spectroscopic, cyclic voltammetric and computational studies.